1993
DOI: 10.1177/104973239300300106
|View full text |Cite
|
Sign up to set email alerts
|

Computer Analysis of Qualitative Data: A Comparison of Three Packages

Abstract: This article describes and compares three computer programs designed to assist in the analysis of narrative text. Ethnograph, GATOR, and Martin were compared in the context of a qualitative study of women and their husbands following mastectomy in order to (a) describe the fit between research purpose and program capabilities and (b) explore the influence, if any, of particular program features on research methods or analysis. The comparison suggests that methodological assistance provided by the programs invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Although little research has been carried out investigating the effects of the packages on research, the small body of existing research indicates that the particular tool used may affect analysis. Walker (1993) compared three programs and concluded that researchers need to pay attention to the fit between methods and the assistance provided by the QDAS.…”
Section: Concerns About the Use Of Qdasmentioning
confidence: 99%
“…Although little research has been carried out investigating the effects of the packages on research, the small body of existing research indicates that the particular tool used may affect analysis. Walker (1993) compared three programs and concluded that researchers need to pay attention to the fit between methods and the assistance provided by the QDAS.…”
Section: Concerns About the Use Of Qdasmentioning
confidence: 99%
“…Folders and file-cards could be unwieldy, but is it a contradiction of terms to analyze qualitative data by means of a computer programme? Many researchers would suggest that it is not (Walker, 1993;Tesch, 1990;Parker and Roffey, 1997;Glesne and Peshkin, 1992;Singh, 1997). From the use of word processors, and databases, to qualitative analysis programmes, there is a large range of software that can assist the data analysis process.…”
Section: Discussionmentioning
confidence: 99%
“…These programs vary enormously in the extent to which a number of analytical activities can be undertaken ( Anderson 1987, Heise 1988, Knafl & Webster 1988, Pfaffenberger 1988, Tesch 1990, Huber & Garcia 1991, Richards & Richards 1991, 1994b, Fielding & Lee 1993, Moseley & Mead 1993, Russell & Gregory 1993, Walker 1993, Weitzman & Miles 1995). As yet, there is no common interface between most packages and the decision to purchase a particular piece of software is a significant one that needs to be made in an informed way ( Lewins 1996).…”
Section: The Use Of Computer Software To Facilitate Data Analysismentioning
confidence: 99%